A binder-free, well-integrated metal–organic frameworks@polypyrrole nanofilm electrocatalyst for highly efficient and selective reduction of carbon dioxide. (December 2022) - Li, Mingyuan; Tang, Mi; Xue, Ping; Dai, Hongmei; He, Tianwei; Wang, Zhengbang
Abstract: Metal–organic frameworks (MOFs) are promising electrocatalysts for carbon dioxide reduction reaction (CO2 RR) due to their designable crystalline structures, large surface area, and atomically dispersed active sites. However, the poor electric conductivity of MOFs, leading to the low utilization of large amounts of active sites, greatly inhibits their practical applications in electrocatalysis. Herein, a binder-free, MOF-based nanofilm electrocatalyst for highly efficient and selective CO2 RR is achieved by well-grafting conductive polypyrrole (PPy) chains into surface-mounted MOF (ZIF-8) nanofilm electrocatalyst based on a combination of the layer-by-layer assembly MOF growth technique and the in-situ electrochemical polymerization method. Experimental and theoretical results confirm that the grafting of PPy not only significantly accelerates the electron transfer for high utilization of active sites but also optimizes the electronic structure of the electrocatalysts for high electrocatalytic activity. As a result, the optimized ZIF-8@PPy nanofilm electrocatalyst exhibits the excellent electrocatalytic CO2 RR performance with a selectivity of 96% and a current density of up to 18 mA/cm 2 at −1.1 V. The strategy in this work has also demonstrated the broad potential application to a variety of other electrochemical purposes. Graphical abstract: Image 1 Highlights: A series of binder-free, well-integrated MOF@PPy nanofilm electrocatalysts for CO2 RR was developed. Both experimental and theoretical evidences reveal the excellent CO2 RR performance of the optimized electrocatalyst. The strategy has also demonstrated the broad potential application to other electrochemical purposes.